Enhancing Fourth Grade IPAS Concept Comprehension through Scientific Reading-Based E-Modules Developed with Exe-Learning - Ning Dainty Restiani; Kartika Chrysti Suryandari; Ratna Hidayah (AL-ISHLAH: Jurnal Pendidikan, 2024)
The integration of technology in 21st-century learning is essential, particularly in science education, where interactive tools can enhance students' understanding of complex concepts. Exe-learning, a platform that supports the creation of interactive educational content, offers features such as quizzes, practice questions, and simulations that aid in concept comprehension. This study employed a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create an interactive electronic module for the IPAS lesson on "Energy Transformation." A nonequivalent control group design was used to assess the e-module's effectiveness. Data were collected using pretest-posttest assessments to evaluate module feasibility and effectiveness, complemented by interviews and observations. Data analysis included N-Gain and Cohen's tests to measure improvement in conceptual understanding. The validation of the e-module showed high feasibility scores: 66% for content, 94% for language, and 86% for media. The N-Gain analysis indicated significant improvement in students' understanding, confirming the module's effectiveness as a learning tool. The findings suggest that the scientifically structured, reading-based e-module promotes critical thinking and actively engages students, leading to improved comprehension of IPAS concepts. The exe-learning-based electronic module demonstrates potential as an effective educational medium, enhancing students' engagement and understanding in the study of energy transformation in elementary science.